2004
DOI: 10.1182/blood-2004-02-0646
|View full text |Cite
|
Sign up to set email alerts
|

Conserved CTL epitopes on the adenovirus hexon protein expand subgroup cross-reactive and subgroup-specific CD8+ T cells

Abstract: Adenoviruses often cause lethal infections in immunocompromised individuals. Adoptive transfer of immune T cells offers a therapeutic option, but this strategy has been hindered by the paucity of information on molecular targets of cellular immunity and by the immunologic heterogeneity of the 51 human adenoviruses, which are grouped from A to F on the basis of genome size, composition, homology, and organization. Clonal analysis of the adenovirus-specific cytotoxic T lymphocyte (CTL) responses of seropositive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 46 publications
7
136
0
1
Order By: Relevance
“…The first line was screened by using CTL assays in part, because a strong response to EBV after switching to BLCLs as APCs made ELISPOT screening difficult to interpret. Three peptides were identified in this line and two of these (SP28 and SP29) shared the overlapping sequence KPYSGTAYNAL, previously identified as being HLA-B*0702-restricted (Leen et al, 2004b). Using SP29, we confirmed that RD0407 also recognized KPYSGTAYNAL presented by B*0702.…”
Section: Minimum Peptide Identificationsupporting
confidence: 58%
See 2 more Smart Citations
“…The first line was screened by using CTL assays in part, because a strong response to EBV after switching to BLCLs as APCs made ELISPOT screening difficult to interpret. Three peptides were identified in this line and two of these (SP28 and SP29) shared the overlapping sequence KPYSGTAYNAL, previously identified as being HLA-B*0702-restricted (Leen et al, 2004b). Using SP29, we confirmed that RD0407 also recognized KPYSGTAYNAL presented by B*0702.…”
Section: Minimum Peptide Identificationsupporting
confidence: 58%
“…The HLA-restriction panel indicated that one or more A*0101-restricted and DRB1*1101-restricted peptides were recognized. Review of the initial small-pool screening showed weak stimulation by SP91 and SP92, and both contain the previously identified A*0101-restricted epitope, TDLGQNLLY (Leen et al, 2004b). Insufficient cells remained for further characterization.…”
Section: Minimum Peptide Identificationmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to EBV and CMV, HAdV-derived epitopes recognized by T cells are only recently coming to be identified. 16,17 Furthermore, HadVinfected cells may escape from recognition by the immune system through several mechanisms. 18 Evidence has been obtained that recovery of immunity after SCT is essential for the elimination of HAdV infection.…”
Section: Immunity and Hadv Infectionmentioning
confidence: 99%
“…This observation indicates that HD-Ad-derived peptides are being shuttled to MHC I pathway and cross-presented in context with MHC class I to induce CD8 ϩ T cell response along with presentation with MHC class II to induce CD4 ϩ T cell response. Five dominant CD8 ϩ T cell epitopes on the capsid hexon protein of adenovirus have been identified and because HD-Ad vector does indeed has the capsid proteins, it is possible that perhaps cross-presentation of these epitopes may play a role in inducing CD8 ϩ T cell responses (27). Our results indicate that perhaps CD8␣ DCs may play a role in cross-presenting HD-Ad-derived epitopes, because this subset of DC undergoes maturation within the draining MLN upon HD-Ad delivery.…”
Section: Discussionmentioning
confidence: 99%